2010
DOI: 10.1111/j.1872-034x.2010.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of ectopic varices in Japan: Results of a survey by the Japan Society for Portal Hypertension

Abstract: Duodenal varices were found in 57 cases, and most of them were located in the descending to transverse parts. There were 11 cases of small intestinal varices and 6 cases of colonic varices, whereas 77 patients had rectal varices, accounting for the greatest proportion (44.5%). Other sites of varices were the biliary tract, anastomotic sites, the stoma, and the diaphragm. Liver cirrhosis was the most frequent diseases (80.3%) underlying ectopic varices. It was noted that patients with rectal varices frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
105
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 25 publications
1
105
0
2
Order By: Relevance
“…Furthermore, patients with rectal varices were frequently noted to have a history of esophageal varices (94.8%) and the majority (87%) had received endoscopic treatment of esophageal varices [23]. There is conflicting evidence regarding the occurrence of rectal varices following treatment of esophageal varices.…”
Section: Pathophysiology Aetiology and Prevalence Of Anorectal Varicesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, patients with rectal varices were frequently noted to have a history of esophageal varices (94.8%) and the majority (87%) had received endoscopic treatment of esophageal varices [23]. There is conflicting evidence regarding the occurrence of rectal varices following treatment of esophageal varices.…”
Section: Pathophysiology Aetiology and Prevalence Of Anorectal Varicesmentioning
confidence: 97%
“…Some studies have suggested that injection sclerotherapy or band ligation of esophageal varices may influence the natural history of ectopic varices. In the case of anorectal varices, this is postulated to be due to development of collateral vessels in the inferior mesenteric venous system following obliteration of supplying vessels (such as the left gastric, posterior gastric or short gastric veins) which ultimately leads to the formation of rectal varices [11,23,24]. The correlation between treatment of esophageal or gastric varices and subsequent formation of anorectal varices has not been conclusively demonstrated.…”
Section: Pathophysiology Aetiology and Prevalence Of Anorectal Varicesmentioning
confidence: 99%
“…However, a large study conducted in Japan by Watanabe et al [14] reported that 95% of patients with rectal varices had a history of esophageal varices and 87% of these patients had previously under gone endoscopic variceal obliteration for esophageal varices. The mechanism of rectal varices after treatment of esophageal or gastric varices is thought to be the result of obliteration of supplying vessels such as the left gastric, posterior gastric and short gastric veins leading to development of collateral vessels of the inferior mesenteric venous system and thus the formation of rectal varices.…”
Section: Pathogenesismentioning
confidence: 99%
“…The mechanism of rectal varices after treatment of esophageal or gastric varices is thought to be the result of obliteration of supplying vessels such as the left gastric, posterior gastric and short gastric veins leading to development of collateral vessels of the inferior mesenteric venous system and thus the formation of rectal varices. In this nationally representative study in Japan, the most frequent afferent vessel to the rectal varices was the inferior mesenteric vein, followed by the superior rectal vein and the efferent vessels included the internal iliac vein and the inferior rectal vein [14] .…”
Section: Pathogenesismentioning
confidence: 99%
“…These constitute upto 5% of variceal bleeds in patients with intrahepatic portal hypertension, and 20% to 30% of those with extrahepatic portal hypertension. [1][2][3] Of all patients with ectopic varices, the frequency according to site are as follows-duodenal varices(32.9%), jejunum(4%), ileum (1.2%), colon(3.5%), rectal (44.5%) and peristomal (5.8%) 4 . Another study shows the prevalence of anorectal varices to be 77.7%, and that they are much more common in patients with noncirrhotic portal hypertension (89.3%).…”
mentioning
confidence: 99%